A density gradient of VAPG peptides on a cell-resisting surface achieves selective adhesion and directional migration of smooth muscle cells over fibroblasts. (May 2018) - Yu, Shan; Zuo, Xingang; Shen, Tao; Duan, Yiyuan; Mao, Zhengwei; Gao, Changyou
Graphical abstract: Abstract: Selective adhesion and migration of smooth muscle cells (SMCs) over fibroblasts (FIBs) is required to prevent adventitia fibrosis in vascular regeneration. In this study, a uniform cell-resisting layer of poly(ethylene glycol) (PEG) with a density gradient of azide groups was generated on a substrate by immobilizing two kinds of PEG molecules in a gradient manner. A density gradient of alkynyl-functionalized Val-Ala-Pro-Gly (VAPG) peptides was then prepared on the PEG layer via click chemistry. The VAPG density gradient was characterized by fluorescence imaging, revealing the gradual enhancement of the fluorescent intensity along the substrate direction. The adhesion and mobility of SMCs were selectively enhanced on the VAPG density gradient, leading to directional migration toward the higher peptide density (up to 84%). In contrast, the adhesion and mobility of FIBs were significantly weakened. The net displacement of SMCs also significantly increased compared with that on tissue culture polystyrene (TCPS) and that of FIBs on the gradient. The mitogen-activated protein kinase (MAPK) signaling pathways related to cell migration were studied, showing higher expressions of functional proteins from SMCs on the VAPG-modified surface in a density-dependent manner. For the first time the selective adhesion and directional migration of SMCs over FIBs was achieved by an elaborative design of a gradient surface, leading to a new insight in design of novel vascular regenerative materials. Statement of Significance: Selective cell adhesion and migration guided by regenerative biomaterials are extremely important for the regeneration of targeted tissues, which can avoid the drawbacks of incorrect and uncontrolled responses of tissue cells to implants. For example, selectivity of smooth muscle cells (SMCs) over fibroblasts (FIBs) is required to prevent adventitia fibrosis in vascular regeneration. Herein we prepare a uniform cell-repelling layer, on which SMCs-selective Val-Ala-Pro-Gly (VAPG) peptides are immobilized in a continuous manner. Selective adhesion and enhanced and directional migration of SMCs over FIBs are achieved by the interplay of cell-repelling layer and gradient SMCs-selective VAPG peptides, paving a new way for the design of novel vascular grafts with enhanced biological performance.